2009
DOI: 10.1063/1.3195062
|View full text |Cite
|
Sign up to set email alerts
|

Study of absorption spectra and (hyper)polarizabilities of SiCn and SinC (n=2–6) clusters using density functional response approach

Abstract: We theoretically investigate the absorption spectra, dipole polarizabilities, and first-order hyperpolarizabilities of SiC(n) and Si(n)C (n=2-6) clusters using the density functional response approach. Similar to other semiconductor clusters such as Si and gallium arsenide (GaAs) clusters, the absorption spectra of the SiC(n) and Si(n)C clusters show long absorption tails in the low-transition-energy region and strong absorption peaks in the high-transition-energy region (>4.0 eV). For the same n, the absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 71 publications
(103 reference statements)
1
17
0
Order By: Relevance
“…From the present work and also from previous investigations [1][2][3], an important remark can be drawn. When predicting the structures of larger Si n C m clusters, the knowledge of the structure of clusters of a smaller size is of limited help.…”
Section: N Gonzalez Szwacki Ja Majewskisupporting
confidence: 76%
See 1 more Smart Citation
“…From the present work and also from previous investigations [1][2][3], an important remark can be drawn. When predicting the structures of larger Si n C m clusters, the knowledge of the structure of clusters of a smaller size is of limited help.…”
Section: N Gonzalez Szwacki Ja Majewskisupporting
confidence: 76%
“…Knowledge of their properties is therefore important for the development of new materials for electronics-related applications. Numerous experimental and theoretical studies have been carried out to investigate equilibrium geometries, relative energies, and vibrational frequencies of small Si n C m clusters [1][2][3]. On a larger scale the computer simulation of SiC crystal growth depends on the quality of the effective potential that is used to model the interactions between the involved atoms.…”
Section: Introductionmentioning
confidence: 99%
“…For wave-function-based methods, the Møller-Plesset second order perturbation theory (MP2) with the aug-cc-pVDZ or 6-31G augmented by the standard diffuse and polarization functions can lead to accurate dipole polarizabilities, which are very close to the results based on highly accurate coupled cluster singles-and-doubles calculations, including a perturbative triples correction for binary semiconductor clusters such as AlP and GaAs clusters [22][23][24]26]. A more detailed discussion of the basis-set and theoretical method dependences of α for small Si and SiC clusters can be found elsewhere [2,8,9,15,16]. In this work, we calculated the polarizabilities by using the coupled perturbed Hartree-Fock (CPHF) approach at the B3LYP/aug-cc-pVTZ level.…”
Section: Computational Detailsmentioning
confidence: 96%
“…The commonly employed laser wavelengths of 1064 (1.16) and 1907 nm (0.65 eV) are significantly different from the first strong resonance absorption energies at which the optical damage and thermal effects possibly occur; thus, the Si 2 C and Si 3 C clusters, as well as the Si 3 and Si 4 clusters [14], are potential candidates for THG nonlinear optical materials in the infrared range. based on the LRDFT calculations [15], respectively. It has been shown that the size of the α value is possibly related to the shape of the cluster or the energy difference between the molecular orbital levels.…”
Section: Basis Set Dependence Of γ || (0)mentioning
confidence: 99%
“…Besides an interesting size-dependence of the α values, a shape-dependence has been also theoretically reported by Jackson et al [4] for the Si n (n = 20 -28) clusters. Our recent theoretical study showed that the α values of the SiC n and Si n C (n = 2 -6) clusters are larger than the bulk polarizability of 3C-SiC and interestingly lie between the dipole polarizabilities of the Si and C atoms [15].For the first-and second-order hyperpolarizabilities (β and γ), a few studies have been performed on the Si n (n = 3 -8 and 10) [Ref. 13 and 17] and Si n C and SiC n (n = 2 -6) [Ref.…”
mentioning
confidence: 97%